Numerical Modelling of Scramjet Combustor - Deepu, M.; Gokhale, S. S.; Jayaraj, S. (Defence Science Journal, 2007)
Numerical modelling of turbulent-reacting flow field of supersonic combustion ramjet(scramjet) combustors are presented. The developed numerical procedure is based on the implicittreatment of chemical source terms by preconditioning and solved along with unstedy turbulentNavier-Stokes equations explicitly. Reaction is modelled using an eight-step hydrogen-airchemistry. Code is validated against a standard wall jet experimental data and is successfullyused to model the turbulent-reacting flow field resulting due to the combustion of hydrogeninjected from diamond-shaped strut and also in the wake region of wedge-shaped strut placedin the heated supersonic airstream. The analysis could demonstrate the effect of interaction ofoblique shock wave with a supersonic stream of hydrogen in its (fuel-air) mixing and reactionfor strut-based scramjet combustors.